The Digital Economy Acceleration to Increase Economic Growth in the Pandemic Era - Lubis, Mhd Rafki; Aziz, Roikhan Mochamad; Yarham, M. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of Fintech and e-commerce during the Covid-19 pandemic has given its blessing. Fintech and e-commerce can be used as a solution to strengthen the economy. Moved by monetary administrations, changes in individuals' ways of life towards digitalization, and backing from the public authority through clear guidelines and legitimate systems. Animun's high movement of people's activities to gadgets has a positive impact on the country in saving the national economy in the midst of the world's economic downturn. The results of research show e-commerce and fintech have played a role in the Indonesian economy during the COVID-19 pandemic, both for businesses, consumers, and the government.